Antidiabetic Biguanides Radiosensitize Hypoxic Colorectal Cancer Cells Through a Decrease in Oxygen Consumption - de Mey, Sven; Jiang, Heng; Corbet, Cyril; Wang, Hui; Dufait, Inès; Law, Kalun; Bastien, Estelle; Verovski, Valeri; Gevaert, Thierry; Feron, Olivier; De Ridder, Mark (Frontiers in Pharmacology, 2018)
Background and purpose: The anti-diabetic biguanide drugs metformin and phenformin exhibit antitumor activity in various models. However, their radiomodulatory effect under hypoxic conditions, particularly for phenformin, is largely unknown. This study therefore examines whether metformin and phenformin as mitochondrial complex I blockades could overcome hypoxic radioresistance through inhibition of oxygen consumption. Material and methods: A panel of colorectal cancer cells (HCT116, DLD-1, HT29, SW480, and CT26) was exposed to metformin or phenformin for 16 hours at indicated concentrations. Afterwards, cell viability was measured by MTT and colony formation assays. Apoptosis and reactive oxygen species were detected by flow cytometry. Phosphorylation of AMP-activated protein kinase (AMPK) was examined by western blot. Mitochondria complexes activity and oxygen consumption rate were measured by seahorse analyzer. The radiosensitivity of tumor cells was assessed by colony formation assay under aerobic and hypoxic conditions. The in vitro findings were further validated in colorectal CT26 tumor model. Results: Metformin and phenformin inhibited mitochondrial complex I activity and subsequently reduced oxygen consumption rate in a dose-dependent manner starting at 3mM and 30μM respectively. As a result, the hypoxic radioresistance of tumor cells was counteracted by metformin and phenformin with an enhancement ratio about 2 at 9mM and 100μM respectively. Regarding intrinsic radioresistance, both of them did not exhibit any effect although there was an increase of phosphorylation of AMPK and reactive oxygen species production. In tumor-bearing mice, metformin or phenformin alone did not show any anti-tumor effect. While in combination with radiation, both of them substantially delayed tumor growth and enhanced radioresponse respectively by 1.3 and 1.5 folds. Conclusions: Our results demonstrate that metformin and phenformin overcome hypoxic radioresistance through inhibition of mitochondrial respiration, and provide a rationale to explore metformin and phenformin as hypoxic radiosensitizers.